(untitled) (Scientific journal of the Fergana State University, 2023)
The article deals with the definition of “argo”, one of the phenomena of speech, based on the interpretation and analysis of local and foreign linguists. It explains the etymology of the word by linguists, its definitions and differences in its interpretation, as well as the examples of how this term is used by members of society (lower, upper) or social groups. In the section of analysis and conclusion of the article, the linguists explain that "argo" can be divided into two (2) directions: a) "argo" is a linguistic phenomenon that can be observed in the speech of low or disreputable people, and b) "argo" is “special words and phrases” used by their representatives.(legal professions).